Editor's Choice – Acute Kidney Injury (AKI) in Aortic Intervention: Findings From the Midlands Aortic Renal Injury (MARI) Cohort Study. (June 2020) - ,; Sidloff, David; Dovell, George; Forsythe, Rachael; Barnett, Loretta; Barnet, Henrietta; Wollaston, Julie; Goodyear, Stephen; Mahmood, Asif; Matharu, Nicholas; Harrison, Seamus; Boyle, Jonathan; et al.
Abstract : Objectives: The incidence of acute kidney injury (AKI) after open (OAR) or endovascular (EVAR) aortic repair is unknown. This research assessed the proportion of patients who develop AKI after aortic intervention using validated criteria, and explored AKI risk factors. Methods: This was a multicentre national prospective cohort study. Eleven centres recruited patients undergoing EVAR or OAR (September 2017–December 2018). Serum creatinine (SCr) and urine outputs were measured over a minimum of 48 h or throughout the index inpatient stay to define post-operative AKI using the Kidney Disease Improving Global Outcomes (KDIGO) criteria. Renal decline at 30 days was calculated using estimated glomerular filtration rate (eGFR) and the Major Adverse Kidney Events (MAKE) 30 day composite endpoint (consisting of: death, new dialysis, > 25% eGFR decline). Results: 300 patients (mean age: 71 years, standard deviation [SD] 4 years; 9% females) were included, who underwent: infrarenal endovascular aneurysm repair (EVAR) 139 patients, fenestrated EVAR (fEVAR) 30, branched EVAR (bEVAR) seven, infrarenal open aneurysm repair (OAR) 98, juxtarenal OAR 26. Overall, 24% of patients developed stage 1 AKI (defined at 48 h as per KDIGO), 2.7% stage 2 AKI and 1% needed renal replacement therapy before discharge. AKI proportions per intervention were: infrarenal EVAR 18%; fEVAR 27%; bEVAR 71%; infrarenal OAR 41%; juxtarenal OAR 63%. Older age (odds ratio [OR] 1.44 for EVAR, 1.58 for OAR), lower baseline eGFR (OR 0.88 EVAR, 0.74 OAR), and ischaemic heart disease (OR 4.42 EVAR, 5.80 OAR) were the main predictors of AKI for infrarenal EVAR and OAR. Overall, 24% developed the MAKE30 endpoint. All patients who died (0.6%) or developed a major cardiac event (5.6%) at one year had developed AKI. Conclusion: AKI and short term renal decline after aortic intervention are common. Age, renal function, and cardiovascular disease are the main risk factors. Research should now focus on AKI prevention in this high risk group.